Hubungan Tingkat Pengetahuan dan Sikap Terhadap Hygiene Sanitasi Pedagang Air Minum Rebusan Skala Rumah Tangga di Kecamatan Belitang I - Rahmi Garmini (IKesT Muhammadiyah Palembang, 2025)
Background: Hygiene sanitation is one of the health efforts to reduce or eliminate factors that cause contamination of drinking water and facilities used for processing, storage, and distribution. Objective: This study aims to determine the relationship between knowledge level and attitudes towards hygiene sanitation among household-scale boiled drinking water traders in Belitang I District in 2024. Method: This research is quantitative with interview and observation methods. The respondents were 30 boiled drinking water traders. Chi-square test was used for statistical analysis. Result: The results show that knowledge level (p=0.001<0.05) and attitude (p=0.005<0.05) are significantly related to hygiene sanitation. Conclusion: There is a significant relationship between knowledge level and attitudes towards hygiene sanitation among household-scale boiled drinking water traders in Belitang I District.